Heterogeneous sensor location model for path reconstruction - Fu, Chenyi; Zhu, Ning; Ling, Shuai; Ma, Shoufeng; Huang, Yongxi (Transportation research. Part B: methodological, 2016)
•A new traffic sensor location problem is developed and solved by strategically placing both passive and active sensors in a transportation network for path reconstruction.•A scalar product operator is introduced to calculate path flows within algebraic framework.•An extension matrix is generated and used to determine if a replacement scheme is able to reconstruct all path flows.•Maximum clique theory is used to determine the upper bound of feasible replacement scheme.•A polynomial-time algorithm is proposed to solve this problem. A new traffic sensor location problem is developed and solved by strategically placing both passive and active sensors in a transportation network for path reconstruction. Passive sensors simply count vehicles, while active sensors can recognize vehicle plates but are more expensive. We developed a two-stage heterogeneous sensor location model to determine the most cost-effective strategies for sensor deployment. The first stage of the model adopts the path reconstruction model defined by Castillo et al. (2008b) to determine the optimal locations of active sensors in the network. In the second stage, an algebraic framework is developed to strategically replace active sensors so that the total installation cost can be reduced while maintaining path flow observation quality. Within the algebraic framework, a scalar product operator is introduced to calculate path flows. An extension matrix is generated and used to determine if a replacement scheme is able to reconstruct all path flows. A graph model is then constructed to determine feasible replacement schemes. The problem of finding the optimal replacement scheme is addressed by utilizing the theory of maximum clique to obtain the upper bound of the number of replaced sensors and then revising this upper bound to generate the optimal replacement scheme. A polynomial-time algorithm is proposed to solve the maximum clique problem, and the optimal replacement scheme can be obtained accordingly. Three numerical experiments show that our proposed two-stage method can reduce the total costs of transportation surveillance systems without affecting the system monitor quality. The locations of the active sensors play a more critical role than the locations of the passive sensors in the number of reconstructed paths.